Study of Charge-Up Processes in Gas Electron Multipliers. (April 2020) - Hauer, P; Urban, S; Flöthner, K; Ball, M; Ketzer, B
Abstract: GEM foils are known to collect charged particles on the polyimide part in its holes during the amplification process. This is accompanied by a change of the effective gain. The effect is commonly known as the "charge-up effect". In order to study this effect, two complementary approaches were chosen. On the one hand, the effect is studied in an iterative simulation that is based on a finite element calculation of the electrostatic environment and Garfield++ which microscopically tracks charged particles. On the other hand, a dedicated test-detector was setup with a single GEM as an amplification stage. In this study, a special focus lies on the different GEM geometries, i.e. the difference between double-conical and single-conical GEMs. A quantitative comparison between simulated and measured values will be given. It can be concluded that the typical time-constant of the gain increase is in the order of 1 × 10 6 initial electrons per hole. For the specific case of a single-conical GEM, it can be shown that the orientation (tapered side pointing upwards or downwards) determines whether the gain increases or decreases.